Gravity wave momentum fluxes from MF and meteor radar measurements in the polar MLT region - Placke, Manja; Hoffmann, Peter; Latteck, Ralph; Rapp, Markus (Journal of Geophysical Research: Space Physics, 2015)
Annual cycles of horizontal winds and gravity wave (GW) momentum fluxes in the mesosphere/ lower thermosphere (MLT) are presented for the medium frequency Doppler radar at Saura (SMF radar, located at 69◦N, 16◦E) for the first time. Four year mean wind and momentum flux fields for 2008 through 2011 clearly show the coupling and interactions between GWs and the mean flow especially in the summer months. GW breaking at mesopause heights results in momentum flux divergence and affects the wind field by forcing a reversal of the wind profile in summer. Height-time cross sections for the individual years (2008 to 2011) illustrate the year-to-year variation of horizontal winds and the vertical fluxes of zonal and meridional momentum. They show similar annual patterns from year to year which are more consistent in the summer months than during winter and have maximum absolute values in 2009. Furthermore, the precise SMF radar measurements give an excellent possibility to evaluate momentum flux estimates from the colocated meteor radar at Andenes. Both radars have different capabilities, and different techniques are applied to derive momentum fluxes. They show comparable results for the 4 year mean annual cycles of horizontal winds and momentum fluxes especially in summer. This holds for both structure and magnitudes in the overlapping heights, where the SMF radar data provide a wider vertical coverage. The best agreement is found for the zonal components of both radars, whereas there are some larger discrepancies in the meridional components, especially in the vertical flux of meridional momentum.